ELIGIBILITY of Dunaliella sp. AS A PRELIMINARY STEP FOR HEAVY METAL TOXICITY TESTS OF MERCURY (Hg) and CHROMIUM (Cr) - Rahmada Anisa Ahmad; Budijono Budijono; Andri Hendrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTHeavy metals in water can be included in hazardous and toxic materials in high concentrations. Mercury (Hg) and Chromium (Cr) are heavy metals that are dangerous when entering water bodies and will affect aquatic organisms. Microalgae are aquatic organisms that have a significant role as the basis of the food chain, as well as one of the parameters of the fertility level of water which is the primary concern because it has a high risk of being exposed to aquatic organisms such as microalgae. One of the microalgae is Dunaliella sp. This research was conducted to determine the ability of Dunaliella sp. as a condition for biota to test heavy metal toxicity. Observations of the growth of Dunaliella sp. were carried out for 14 days to see the entire growth phase of Dunaliella sp. The results of this study show that there are five life phases of Dunaliella sp., namely the lag phase, the acceleration phase, the exponential phase, the retardation phase, and the death  phase.   Dunaliella sp. qualified  as a test biota for heavy metal toxicity testing according to the Asean-Canada Cooperative Program on Marine Science Phase II. The cell density of  Dunaliella sp. on day four or at the beginning of the exponential phase is 1.36 x 10 6 cells/ ml. It can be seen that the cell density of Dunaliella sp. exceeds the minimum limit (1x106 cells /ml).Keywords : Dunaliella sp., , Exponential, Density  Phytoplankton, Toxicity test